Quasi and dynamic impact performance of hybrid cross-ply banana/glass fibre reinforced polypropylene composites - Dhar Malingam, Sivakumar; Zulkafli, Norizzati; Sheikh Md Fadzullah, Siti Hajar; Razali, Nadlene (Institute of Physics Publishing Ltd., 2019)
Natural fibres has been in demand as a replacement of synthetic fibres. However, natural fibres have disadvantages such as low mechanical properties compared to synthetic fibres, weak matrix to fibre adhesion and low thermal stability. Therefore, using natural fibres as a single reinforcement is inadequate to satisfy the technical needs of the composite. Hybridisation between natural and synthetic fibres can enhance the properties by taking the advantages of each of the individual fibres. This paper presents the hybridisation effect between banana and glass fibre. The low-velocity impact performance of hybrid cross-ply banana/glass fibre reinforced polypropylene composites were investigated and compared with quasi static indentation. Four types of stacking sequences composites were manufactured using hot compression moulding method, and the test was carried out according to American Society for Testing and Materials (ASTM) D6264 for quasi-static indentation and ASTM D7136 for low-velocity impact. The results revealed that the incorporation of glass fibre in banana fibre reinforced composite leads to higher energy absorption and improved the overall impact performance.